Comparison of SIRIM guideline with DataOne Asia disaster recovery plan (DRP) / Ele Elyiana Dul Ngajis - Dul Ngajis, Ele Elyiana (2007)
The biggest disaster in the world, Tsunami that happen to most of the Asia country and Katrina hurricane that had attack some U.S. country make the researcher come out with the title of disaster recovery plan. This is the comparison studies, where the researcher compare either the DataOne Asia (M) Sdn. Bhd. Disaster Recovery Plan (DRP) follows the SIRIM guideline or not. The research findings show that the DataOne Asia DRP had follows all the SIRIM disaster recovery plan guideline. This research will help other organization knows how to follow SIRIM guideline in developing the Disaster Recovery Plan.